Chasing Captain Canada: National Identity Challenged Through Superheroes In Canadian Comic Books - Redford, Jasmine (2020)
This thesis explores the connections between nationalism and the superheroic effigy in domestically produced Canadian superhero comics, with an eye on how Indigenous superhero comics published within Canada may enrich or complicate this landscape. Domestically produced comics and/or graphic novels are defined in this thesis as ones authored and published within Canada. Canadian-produced comics often fail to reach the heights they grope towards: an uncomplicated heroism. In this thesis, heroism is separated from Canadian heroism, which is further troubled through visual and textual representations of nationalisms—maple leaves, arctic climates—and expressions and appropriations of Indigeneity as it pertains to the superhero. These Canadian nationalisms, dovetailing with the supposed Canadian inferiority complex, have slowed down the growth of this genre while simultaneously leaving room for it to expand through the Canadian compulsion to trouble its own nationalisms. Unsettled nationalisms, as they appear in superhero comics—a canon that has traveled the spectrum of gentle incredulity to effigy—prompt Canadians to ask themselves if they have a need for superheroes, or if Canadian superheroes can only fill the roles of super defenders. The thesis examines the superheroes Nelvana from Adrian Dingle’s Nelvana of the Northern Lights (1941), Captain Canuck from Richard Comely’s Captain Canuck (1975), Northguard from Mark Shainblum and Gabriel Morrissette’s New Triumph Featuring Northguard (1984), and Kagagi from Jay Odjick’s (Kitigan Zibi Anishinabeg) Kagagi: The Raven (2010). An exploration of these comics, supported by comic book theory, theories of nationalism in Canadian literature, and scholarship on representations of Indigenous peoples in graphic literatures, shows that the text, the art, and the intersections of both express and challenge outlooks on Canadian heroic figures, while the perspectives of Indigenous people living in Canada both adhere to and complicate these conclusions.